Protein Viability on Au Nanoparticles during an Electrospray and Electrostatic-Force-Directed Assembly Process. (31st January 2010) - Mao, Shun; Lu, Ganhua; Yu, Kehan; Chen, Junhong
Abstract : We study the protein viability on Au nanoparticles during an electrospray and electrostatic-force-directed assembly process, through which Au nanoparticle-antibody conjugates are assembled onto the surface of carbon nanotubes (CNTs) to fabricate carbon nanotube field-effect transistor (CNTFET) biosensors. Enzyme-linked immunosorbent assay (ELISA) and field-effect transistor (FET) measurements have been used to investigate the antibody activity after the nanoparticle assembly. Upon the introduction of matching antigens, the colored reaction from the ELISA and the change in the electrical characteristic of the CNTFET device confirm that the antibody activity is preserved during the assembly process.